The Puzzle of Functional Recovery in Schizophrenia-Spectrum Disorders—Replicating a Network Analysis Study. (10th March 2022) - Moura, Bernardo Melo; Isvoranu, Adela-Maria; Kovacs, Veronika; Van Rooijen, Geeske; Van Amelsvoort, Therese; Simons, Claudia J P; Bartels-Velthuis, Agna A; Bakker, P Roberto; Marcelis, Machteld; De Haan, Lieuwe; Schirmbeck, Frederike
Abstract: Background and hypothesis: Recovery from psychosis is a complex phenomenon determined by an array of variables mutually impacting each other in a manner that is not fully understood. The aim of this study is to perform an approximated replication of a previous network analysis study investigating how different clinical aspects—covering psychopathology, cognition, personal resources, functional capacity, and real-life functioning—are interrelated in the context of schizophrenia-spectrum disorders. Study design: A sample of 843 subjects from a multisite cohort study, with the diagnosis of a schizophrenia-spectrum disorder, was used to estimate a network comprising 27 variables. The connectivity and relative importance of the variables was examined through network analysis. We used a quantitative and qualitative approach to infer replication quality. Study results: Functional capacity and real-life functioning were central and bridged different domains of the network, in line with the replicated study. Neurocognition, interpersonal relationships, and avolition were also key elements of the network, in close relation to aspects of functioning. Despite significant methodological differences, the current study could substantially replicate previous findings. Conclusions: Results solidify the network analysis approach in the context of mental disorders and further inform future studies about key variables in the context of recovery from psychotic disorders.